2011
DOI: 10.1111/j.1365-2222.2011.03863.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity is associated with increased asthma severity and exacerbations, and increased serum immunoglobulin E in inner‐city adults

Abstract: Obesity in inner-city adults may be both a risk and exacerbating factor for atopic asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
54
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 66 publications
1
54
1
1
Order By: Relevance
“…21 Epidemiologic studies have consistently found a strong link between asthma and obesity. [21][22][23][24] However, previous studies found conflicting results about whether AD is associated with overweight or obesity. This has important clinical ramifications, because obesity may be a modifiable risk factor for and/or comorbidity of AD.…”
mentioning
confidence: 97%
“…21 Epidemiologic studies have consistently found a strong link between asthma and obesity. [21][22][23][24] However, previous studies found conflicting results about whether AD is associated with overweight or obesity. This has important clinical ramifications, because obesity may be a modifiable risk factor for and/or comorbidity of AD.…”
mentioning
confidence: 97%
“…Most studies on the association between BMI and allergic disorders in children are in high-income countries [24][25][26] while little is known on this association in children from low-to-middle income countries. Among high-SES school children in this study, we also found that skin reactivity to cockroach and BMI were positively associated with the increased risk of eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Extrapulmonary factors including tobacco smoking [30], psychological dysfunction [31], rhinosinusitis/nasal polyps [32], obesity [33] and gastro-oesophageal reflux disease [34] have been associated with recurrent severe exacerbations, and current management guidelines advocate identification and management of these conditions [2]. In identifying determinants of not attaining 'well controlled asthma' in the Gaining Optimal Asthma controL (GOAL) study, the greatest odds ratio was current smoking when compared with never smokers (odds ratio 2.8) [35].…”
Section: Risk Factors For Exacerbationsmentioning
confidence: 99%